Pengaruh Partisipasi Dalam Penyusunan Anggaran Terhadap Kinerja Manajerial dan Motivasi Sebagai Variabel Intervening - Mohamad Nasir (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The research objective is to examine the effect of budget participation on managerial performance and motivation as intervening variable. These respondents involve managers those participate in preparing budget in public manufacturing firms. Data were collected by using random sampling method and analyzed by structural equation model. This research finds that budget participation has positive and significant effect on motivation and managerial performance. Meanwhile motivation has positive and significant effect on managerial performance. This research has limitations. First, the sample of this research is managers that participate in preparing budget. Second, data were analyzed by using path analysis that has limitation. So, future research suggests by using simultaneous equation to eliminate errors. This model is called structural equation model.